2019
DOI: 10.23960/j.hptt.219101-108
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF BAGWORM Pteroma pendula Joannis ATTACK ON THE DECREASE IN OIL PALM PRODUCTIVITY

Abstract: Outbreak of oil palm bagwormPteroma pendula has been reported within the last few years in several plantations in North Sumatra. A study was conductedto determine the impact of P. pendula attacks on oil palm productivity. Aerial photograph was taken in November 2016 andanalyzed to determine the level of damage on each palm canopy. The damage symptoms were classified onto healthy palms ascontrol plants (score 0), mild (score 1), moderate (score 2), severe (score 3), and very severe (score 4). The sample palms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
0
18
0
4
Order By: Relevance
“…Hama dapat menyerang kelapa sawit pada fase pembibitan sampai budidaya di lapangan. Sebagian besar hama yang menyerang kelapa sawit berasal dari kelompok serangga terutama dari ordo Acrididae)] (Febriani et al, 2020;Priwiratama et al, 2019;Kamarudin & Wahid, 2010). Serangga hama tersebut menyerang hampir semua bagian tanaman kelapa sawit mulai dari akar, batang, tandan buah, dan daun.…”
Section: Pendahuluanunclassified
“…Hama dapat menyerang kelapa sawit pada fase pembibitan sampai budidaya di lapangan. Sebagian besar hama yang menyerang kelapa sawit berasal dari kelompok serangga terutama dari ordo Acrididae)] (Febriani et al, 2020;Priwiratama et al, 2019;Kamarudin & Wahid, 2010). Serangga hama tersebut menyerang hampir semua bagian tanaman kelapa sawit mulai dari akar, batang, tandan buah, dan daun.…”
Section: Pendahuluanunclassified
“…In general, minor damage to the fronds of 10-13% led to a decrease in production of 33-40% [1]. Priwiratama et al reported that Pteroma pendula bagworm attacks were able to reduce production by 36.35% [2]. Meanwhile, Metisa plana caterpillar attacks in Malaysia caused yield losses of up to 43% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The common control methods of these bagworms were limited by using synthetic chemical insecticides. The use of synthetic chemical insecticides is preferred because it is faster to control pest populations and easy to use [4]. However, the use of synthetic Insecticides continuously is very unwise and could cause various negative impacts on the environment.…”
Section: Introductionmentioning
confidence: 99%